Imitation and politics : redesigning modern Germany - Jacoby, Wade 1964-2020 (Cornell Univ. Press, 2000)
"Following World War II, Allied occupying forces sought to build institutions in Germany that were the functional equivalents of the ones they valued at home. They encouraged the development of selected German organizations that became co-architects of the post-war society. Several decades later, by contrast, policymakers in Bonn used exact rather than functional imitation, and they ignored regional interests when redesigning East German society. For both cases, Jacoby focuses on attempts to reform industrial relations and secondary education." "For innovations to be "pulled in" from abroad, Jacoby argues, local civic groups must participate in and benefit from the institution-building process. In addition, the state imposing the transfer must have a flexible strategy. By looking at international examples, Jacoby provides further evidence that political imitation is at heart a process of coalition building."--BOOK JACKET.